SYNTHESIS OF 2 – (1, 3 – SUBSTITUTED – 1 H- PYRAZOL-4-Y1) – 1H- BENZO (D) OXAZOLES BY USING AMMONIUM CHLORIDE; AS A MILD AND EFFICIENT CATALYST - CH.MADHU; S.HARIPRASAD; A.HYMAVATHI; K.RAMANJANEYULU; J.SANTHOSH KUMAR; B.VENKATESWARA RAO (International Journal of Pharma and Bio Sciences, 2016)
An efficient and simple procedure has been developed for the synthesis of 2- (1,3- substituted–1H- pyrazol–4-y1)–1H -benzo(d)oxazoles from the condensation of 3–Aryl-1- Phenyl –1H – pyrazole – 4- carabaldehyde with 2- aminophenol using ammonium chloride, which is a very inexpensive, metal free, readily available reagent. The target compounds were obtained in good yields under fairly mild reaction conditions at room temperature.